Lukianos és Kallistratos műtárgyleírásai: szöveg és hagyomány - Hajdú, Attila (Antikvitás & Reneszánsz, 2018)
Lucian of Samosata’s descriptions of works of art are invaluable for the studying of the Classical and post-Classical Greek sculpture. The Second Sophistic author does not only give accurate and detailed descriptions about Greek sculptures and paintings, but as a real connoisseur of art he also judges them from the perspective of aesthetics. In the first main part of my paper, I will focus on the characteristics of his descriptions by analyzing the nude figure of Aphrodite of Cnidus made by Praxiteles and the ‘eclectic’ portrait of Panthea. The aim of the second part of my paper is to present the essential features of Ekphraseis of the sophist Callistratus who lived in Late Antiquity (IV–Vth century AD). It has been disputed if Callistratus’ work inspired by the rhetorical exercises has any art history values. This paper also raises the question how the tradition of both Lucian and Callistratus could influence the description of the sculpture ‘Apollo Belvedere’ included in Winckelmann's epoch-making Art History.